Strengthening Critical Thinking Skills of Prospective Teachers Through Applications Of Vedic Mathematics (International Journal of Scientific Research and Management (IJSRM), 2017)
Good teachers form the foundation of good schools, and improving teachers‟ skills and knowledge is one of the most important investments of time and money that local, state, and national leaders make in education. Our changing goals for learning, coupled with shifts in curriculum emphasis and a deeper understanding of teacher learning and student thinking, have led to new findings about the impact of teacher professional development and how best to sharpen teachers‟ skills and knowledge. Teachers are expected to teach as per the curriculum, take care of all round development of children, develop abilities such as learning how to learn, problem solving, creative thinking, which are crucial for living effectively in the world rapidly changing with the developments in science and technology. A person who does not possess the skills and competencies required for the tasks expected of the teacher cannot be called a teacher. What matters most is what teachers learn. Professional development should improve teachers‟ knowledge of the subject matter that they are teaching, and it should enhance their understanding of student thinking in that subject matter.